A remote‐controlled vascular interventional robot: system structure and image guidance. Issue 2 (21st March 2013) - Meng, Cai; Zhang, Jun; Liu, Da; Liu, Bo; Zhou, Fugen
Abstract Background Robot‐assisted vascular interventional surgery (VIS) enables the surgeon to teleoperate a catheter in a safe cabinet, such that exposure to X‐ray radiation is reduced. For safe and accurate teleoperation, system structure and image guidance is important. Methods The system structure of the developed remote‐controlled vascular interventional robot (RVIR) and its image guidance system (IGS) are introduced. RVIR is based on a master–slave structure. Key technologies of IGS are addressed, including C‐arm calibration, distortion correction, catheter localization and 3D vasculature reconstruction. Results Experiments show that the RMS error of distortion correction is 0.35 pixels, and 0.53 mm for distance reconstruction. The error in catheter localization between the IGS and the encoders is small. In vitro and in vivo tests verified the feasibility of RVIR. Conclusions Experiments indicate that the RVIR is feasible and valid to help the surgeon perform VIS remotely; the function and reconstruction accuracy of IGS can satisfy the surgeon's requirement to guide the RVIR. Copyright © 2013 John Wiley & Sons, Ltd.